Efficient access to amides of the carborane carboxylic acid [1-(COOH)–CB11H11]−. Issue 40 (19th June 2018) - Shen, Yunjun; Zheng, Kai; Dontha, Rakesh; Pan, Yani; Liu, Jiyong; Duttwyler, Simon
Abstract : The preparation of the carborane acid chloride [1-(COCl)–CB11 H11 ] − from the carboxylic acid [1-(COOH)–CB11 H11 ] − and subsequent amide formation are reported. Abstract : The preparation of the carborane acid chloride [1-(COCl)–CB11 H11 ] − from the carboxylic acid [1-(COOH)–CB11 H11 ] − is reported. This acid chloride exhibits remarkable inertness towards moisture and can be stored under ambient conditions for several months. Reaction with amines affords secondary and tertiary carborane amides [1-(CONR 1 R 2 )–CB11 H11 ] − in moderate to high yields under mild conditions. Two of the amide products were characterized by X-ray crystallography in addition to spectroscopic analysis. Preliminary studies show that the amides can be reduced to the corresponding amines and that the acid chloride has the potential to serve as a starting material for carborane ester formation.